Frequência e genogrupagem do Torque teno virus em pacientes sob tratamento dialítico e transplantados renais : uma associação com moléculas HLA. - Takemoto, Angélica Yukari (2012)
Torque teno virus (TTV) was discovered by Nishizawa et al. (1997) in the bloodstream of Japanese patients with post-transfusion hepatitis with elevated alanine aminotransferase and of unknown etiology. Colonizing the general population, its pathological aspect remains under discussion. Through phylogenetic analysis, we identified more than 40 genotypes, sorted into five major groups found in many clinical cases of humans. Patients undergoing dialysis and kidney transplant stood out, as these populations have risk factors such as multiple blood transfusions and low immunity, which may increase the frequency of occurrence of this microorganism. In the aspect of immunity, changes in the immune response of patients, from the Human Leukocyte Antigens (HLA), can motivate the susceptibility or resistance to various autoimmune and infectious diseases. However, there are no references to the relationship between the virus entrainment and HLA typing. Thus, this study aimed to investigate the prevalence of TTV in blood samples of patients on dialysis and kidney transplanted patients enrolled in a dialysis unit of a hospital in the municipality of Maringá, correlating it with the HLA typing. The period of data collection and laboratory procedures was from January to June 2011, with patients enrolled in the dialysis center at Hospital Santa Casa de Misericordia, located in Maringá - Paraná. A sample of 10 mL of peripheral blood was obtained by venipuncture, to perform the DNA extraction. We employed two techniques of Polymerase Chain Reaction (PCR), one for the identification of the microorganism and the other for the detection of genomic groups. The HLA genetic profile was obtained using the kit LABType® SSO One Lambda, grouped with Luminex technology. Among the 118 patients on dialysis, the frequency of TTV was 36.4% and among 50 renal transplanted recipients was 54.0%. In both population samples, no significant association was found between the microorganism presence with the following variables: age and sex of the patient, treatment time, concomitant presence with hepatitis B virus and blood transfusions (p>0,05). With respect to genomic groups, the predominant genogroup was 5, in addition to the presence of a homogeneous pattern between the samples of TTV. As for HLA typing, it was not observed association of protection and susceptibility of genes of class I and II and the entrainment of the microorganism, sometimes among dialysis patients, sometimes among renal transplanted recipients. Thus, the issues related to viral biology, pathogenicity and its clinical significance among these patients require further elucidation. Moreover, the absence of studies about the association between the TTV frequency and the molecules of the HLA complex, and the great variability of the polymorphism of this system, marks and drives the need for further research on the involvement of HLA in the pathogenesis of infection and entrainment of TTV.